The relation between Blood Vessel Expansion with Nitric Oxide Test As Indicator and Some Bio – kinematical and physiological variables in Advance Long Distance Runners - Hazim, Abeer; Mohammed, Jumaa (Journal of Physical Education, 2019)
One of the modern scientific discoveries is the discovery of nitric oxide that is produced in blood vessels and works in expanding them thus leads to better blood flow and increased oxygen that produces energy. The importance of the research lies in this test being very easy to use and the result is shown by saliva saving effort, time and money. The research aimed at using nitric oxide test in sports. The researchers hypothesized significant relation between nitric oxide test and blood pressure in long distance runners. The researchers concluded statistical differences between nitric oxide test and blood pressure measurement in advance long distance runners. They finally recommended using nitric oxide test instead of hemoglobin test and blood pressure measurement for evaluating blood vessel expansion in long distance runner.